PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KETERSEDIAAN SARANA DAN PRASARANA TERHADAP KEPUASAN KERJA GURU - Mawaddah, Mawaddah; Harapan, Edi; Kesumawati, Nila (Graduate Program Magister Manajemen Pendidikan, 2021)
This study examined the influence of leadership of headmaster and facilities toward job satisfaction to the Public Elementary School of Tanjung Raja. This study was kuantitatif method. The population was all the teacher of State Elementary School of Tanjung Raja. Sample taken by cluster sampling method was 86 teachers. The data collected by documentation, questionaire and observation. The data were analyzed by using regresi with SPSS programme. This study showed there was any influance leadership of headmaster toward job satisfaction to the state Elementary School of Tanjung Raja. There was any influence of facilities toward job satisfaction to the state Elementary School of Tanjung Raja and The conclusion there was any influence of leadership of headmaster and facilities toward job satisfaction to the state Elementary School of Tanjung Raja.